Anthropometric parameters and the incidence of atrial fibrillation in older people: the PRO.V.A study. Issue 7 (13th February 2017) - Trevisan, Caterina; Maggi, Stefania; Curreri, Chiara; Nante, Giovanni; Noale, Marianna; De Rui, Marina; Perissinotto, Egle; Sartori, Leonardo; Zambon, Sabina; Crepaldi, Gaetano; Manzato, Enzo; Sergi, Giuseppe
Abstract : Background: Atrial fibrillation (AF) has been associated with body size and central obesity, but the impact of different anthropometric measures in this relationship has been inadequately investigated. Hypothesis: In this study, we examined the association between baseline anthropometric parameters with the incidence of AF in older people, hypothesizing that body size could impact the onset of AF more than fat distribution. Methods: Our study included 1764 participants with a mean age of 74.3 ± 6.9 years and no AF at baseline. Body mass index (BMI), body height, body surface area (BSA), waist and hip circumference, waist‐to‐stature ratio, waist‐to‐hip ratio, and mid–upper arm circumference (MUAC) were measured by trained physicians. AF was assessed after a 4.4‐year follow‐up. Results: There were 115 new cases of AF observed after the follow‐up. Taking lower values of these measures for reference, the adjusted AF risk was 2.42 (95% confidence interval [CI]:1.88‐3.12) for the highest stature quartile, 1.36 (95% CI:1.15‐1.62) for BMI ≥30 kg/m 2, 2.12 (95% CI:1.73–2.59) for the highest BSA quartile, 1.38 (95% CI: 1.21‐1.56) for higher MUAC, and 1.39 (95% CI: 1.23‐1.58, P < 0.0001) for higher hip circumference values. Central obesity did not seem to relevantly predict the onset of AF in our sample. Stature revealed the strongest impact on the onset of AF (5% higher risk of developing AF per 1 cm increase in height). Conclusions: Body size, particularly tall stature and obesity, but not fat distribution, seems to be associated with the risk of AF in the elderly.